Epidemiological and clinical aspects of the coronavirus disease 2019 (COVID-19) outbreak based on global data: A review article - Mohammad-Rafi Bazrafshan; Ahmadreza Eidi; Zahra Keshtkaran; Nasrin Shokrpour; Parisa Zand; Hamed Delam (Shiraz University of Medical Sciences, 2020)
Background: In December 2019, a series of pneumonia cases of unknown cause appeared in Wuhan, China, which was very similar to viral pneumonia. In late January 2020, the World Health Organization named this disease  the sixth public health emergency of international concern due to an increase in the number of COVD-19 cases. This study was designed to determine  different epidemiological and clinical aspects of COVID-19 worldwide. Methods: This is a review study. We searched for articles related to COVID-19 from December 20, 2019 to June 05, 2020. Two researchers performed the search separately, and finally articles containing information on coronavirus, its mortality and epidemiology and clinical characteristics of the patients were selected for review and extraction. Results: The results of various studies show that the most common symptoms of the disease include fever, cough and fatigue, and the most common respiratory symptom is Rhinorrhoea. Transmission occurs primarily when an infected person sneezes or coughs through respiratory droplets, such as the spread of influenza and other respiratory pathogens. Some studies have reported that the COVID-19 incubation period is an average of 4.6 days, ranging from 1.2 to 11.1 days and can potentially be asymptomatic. Conclusion: The significant increases in the morbidity and mortality necessitate prevention and control activities by educating people on important health issues such as staying at home, using clean masks and gloves, as well as performing proper and timely medical interventions.